The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.juro.2016.09.080
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal Polyuria in Older Women with Urge Urinary Incontinence: Role of Sleep Quality, Time in Bed and Medications Used

Abstract: Purpose Nocturia is common and bothersome in older adults especially those who are also incontinent. Since nocturnal polyuria (NP) is a major contributor, we examined factors associated with NP in this population to identify those possibly amenable to intervention. Method We analyzed baseline data from two previously-completed studies of urge urinary incontinence (UUI). The studies involved 284 women (mean 72.9 ±7.9 years) who also completed 3-day voiding diaries. Participants with nocturnal polyuria index (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
3
6
0
Order By: Relevance
“…This may also have been because severe LUTS, including concomitant urge incontinence and nocturia, can be improved by increasing the dose of tamsulosin. This result is consistent with that of a previous investigation, in which Tyagi et al [21] reported an association between urge incontinence and nocturnal polyuria in older women. Further studies should be conducted into whether interventions to reduce nocturnal polyuria are associated with the duration of uninterrupted sleep and urge incontinence.…”
Section: Discussionsupporting
confidence: 94%
“…This may also have been because severe LUTS, including concomitant urge incontinence and nocturia, can be improved by increasing the dose of tamsulosin. This result is consistent with that of a previous investigation, in which Tyagi et al [21] reported an association between urge incontinence and nocturnal polyuria in older women. Further studies should be conducted into whether interventions to reduce nocturnal polyuria are associated with the duration of uninterrupted sleep and urge incontinence.…”
Section: Discussionsupporting
confidence: 94%
“…22 Based on the findings of the present study, NP may be improved by controlling blood pressure to lower it during sleep. Regarding antihypertensive agents, angiotensin receptor blockers (ARBs) have been reported to be effective for NP, 23 while Ca blockers may conversely cause nocturia. [24][25][26][27][28] However, the previous report on ARBs for NP was found to be effective only in women, and no significant difference in ARBs use was observed only in male patients aged 65 years or older in this study.…”
Section: Discussionmentioning
confidence: 99%
“…And quitting smoking has been regarded as one of the lifestyle changes to improve UI (John, 2020). The polyuria caused by renal dysfunction can also lead to the occurrence of UI (Tyagi et al, 2017), which reminding clinician of alerting the diuretics in patients with CKD.…”
Section: Discussionmentioning
confidence: 99%